Efficacy of a Direct Aspiration First-Pass Technique (ADAPT) for Endovascular Treatment in Different Etiologies of Large Vessel Occlusion: Embolism vs. Intracranial Atherosclerotic Stenosis - Liao, Geng; Zhang, Zhenyu; Zhang, Guangzhi; Du, Weijie; Li, Chaomao; Liang, Hanxiang (Frontiers in Neurology, 2021)
Background and Aims: Aspiration thrombectomy is an effective method of recanalizing large vessel occlusion (LVO). However, the efficacy of a direct aspiration first-pass technique (ADAPT) for recanalization of LVO of different etiologies is not properly understood. Methods: The prospectively collected database on ADAPT was reviewed retrospectively. We defined two groups of enrolled patients: the embolism-related occlusions (EMB-O) group and the intracranial atherosclerotic stenosis (ICAS)-related occlusion (ICAS-O) group. Baseline characteristics, procedural variables, and post-procedural variables were collected. Multivariate logistic regression analysis was used to identify first-pass recanalization predictors. Results: Of 114 registered patients, 94 were eligible for this study (51 patients in the EMB-O group and 43 patients in the ICAS-O group). Achieving successful reperfusion immediately after direct aspiration was more frequent in the EMB-O group than in the ICAS-O group (64.71 vs. 27.91%, respectively, p = 0.006), with fewer additional rescue treatments needed (35.29 vs. 70.09%, respectively, p = 0.001). The EMB-O group also showed a higher final successful reperfusion rate (96.8 vs. 74.41%, p = 0.006). However, the 90-day good functional outcomes were not affected by the groups. Independent predictors of first-pass success of aspiration included the isolated middle cerebral artery site of occlusion, embolic etiology, and use of larger bore catheters. Conclusions: The efficacy of ADAPT recanalization approach was better in EMB-O than in ICAS-O. In case of embolic etiology and the isolated MCA site of occlusion, using a larger aspiration catheter for direct aspiration thrombectomy may be reasonable.